2010
DOI: 10.1111/j.1365-2133.2010.09672.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of pemphigus vulgaris IgG to antigens in desmosome core domains excludes immune complexes rather than directly splitting desmosomes

Abstract: These results suggest that the PV IgG/Dsg3 immune complexes are excluded from the desmosomal core domain rather than directly splitting the desmosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
2
28
1
1
Order By: Relevance
“…However, this direct access of IgG to Dsg3 within desmosomes does not always appear to be operative. Our studies have revealed that even if halfdesmosome-like structures are bound with PV-IgG-gold particles in low Ca 2þ medium, these half-desmosomes covered with PV-IgG-gold particles do not inhibit the formation of desmosomes; instead, the gold-decorated half-desmosomes are coupled to form complete desmosomes during Ca 2þ switch, with gold particles being sandwiched in the core of resultant desmosomes [53] (Fig. 7).…”
Section: Two Principal Hypotheses For the Pathomechanisms Of Pemphigumentioning
confidence: 91%
See 1 more Smart Citation
“…However, this direct access of IgG to Dsg3 within desmosomes does not always appear to be operative. Our studies have revealed that even if halfdesmosome-like structures are bound with PV-IgG-gold particles in low Ca 2þ medium, these half-desmosomes covered with PV-IgG-gold particles do not inhibit the formation of desmosomes; instead, the gold-decorated half-desmosomes are coupled to form complete desmosomes during Ca 2þ switch, with gold particles being sandwiched in the core of resultant desmosomes [53] (Fig. 7).…”
Section: Two Principal Hypotheses For the Pathomechanisms Of Pemphigumentioning
confidence: 91%
“…These sandwiched antibodies are also supposed to include anti-Dsg3 antibodies against Ca 2þ -dependent epitopes at N-terminal domain, because at least 30 minutes are required for the formation of desmosomes after Ca 2þ switch and few minutes are enough for antibodies to bind to antigens. On the other hand, time-lapsed immunofluorescence studies demonstrate that the PV-IgG, which penetrates into the core domain of desmosomes and binds to Dsg3 during the first 2-minute incubation with PV-IgG (anti-Dsg3), is mostly excluded from the desmosomes within 5 hours following washing and incubation with a PVIgG-free medium [53] (Fig. 8).…”
Section: Two Principal Hypotheses For the Pathomechanisms Of Pemphigumentioning
confidence: 96%
“…Using cultured keratinocytes, PVIgG and AK23 treatments induced internalization and depletion of Dsg 3 from cell membrane (Triton-X-100 soluble) fractions within 30 -60 min and depletion of Dsg3 from cytoskeleton (Triton-X-100 insoluble) fractions including desmosomes within later 24 -48 h Aoyama et al, 2010;Calkins et al, 2006: Sato et al, 2000Williamson et al, 2006;Yamamoto et al, 2007). These results suggest that the fi rst depletion of Dsg3 from non-desmosomal pool is linked to the secondary depletion of Dsg3 from desmosomes, causing a decrease in cell adhesion strength.…”
Section: Desmoglein Internalization/disassembly Conceptmentioning
confidence: 99%
“…The other mechanism by which pemphigus autoantibodies destroy the functions of their specifi c target antigens is depletion of Dsgs from desmosomes at protein levels, leading to the generation of fragile desmosomes Aoyama et al, 2010;Kitajima, 2013). Using cultured keratinocytes, PVIgG and AK23 treatments induced internalization and depletion of Dsg 3 from cell membrane (Triton-X-100 soluble) fractions within 30 -60 min and depletion of Dsg3 from cytoskeleton (Triton-X-100 insoluble) fractions including desmosomes within later 24 -48 h Aoyama et al, 2010;Calkins et al, 2006: Sato et al, 2000Williamson et al, 2006;Yamamoto et al, 2007).…”
Section: Desmoglein Internalization/disassembly Conceptmentioning
confidence: 99%
“…23,24 Polyclonal anti-Dsg3 IgG antibodies in sera from pemphigus patients and pemphigus model mice are now widely accepted to comprise mixtures of both pathogenic and nonpathogenic IgGs, based on the results of studies using monoclonal antibodies from patients and mice. 5,6 A growing number of studies suggest that inhibition of signaling pathways such as MAPK and c-Myc, [25][26][27] as well as endocytic processing of Dsg3, 28,29 can prevent loss of keratinocyte adhesion in PV IgG-treated cells. Overall, these studies suggest that PV IgG may modulate the assembly and disassembly kinetics of desmosomes, and that modifying keratinocyte signaling pathways can blunt keratinocyte sensitivity to PV IgG.…”
Section: Discussionmentioning
confidence: 99%